An Analysis of Intrinsic and Extrinsic Elements in MONKEY MAJIK’s Songs - Luticia M T Gusmao; Mikhael Misa; Hesni Neno (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study aims to explain the intrinsic and extrinsic elements in the lyrics of Monkey Majik's songs to the readers. The research method used is a descriptive, qualitative approach with a textual analysis. The research object consists of song lyrics, which are analyzed by classifying the data into tables, lyric quotes, and narrative descriptions for better understanding. The findings show that the lyrics of Monkey Majik’s songs contain intrinsic elements such as theme, tone, and setting, as well as extrinsic elements such as cultural background, social values, and educational values. The researcher concludes that Monkey Majik's songs hold deep meanings and life values conveyed through poetic language and diverse cultural backgrounds, making them worthy of being considered literary works that emotionally touch the audience.